A novel bio-nano emulsion fuel based on biodegradable nanoparticles to improve diesel engines performance and reduce exhaust emissions. (September 2018) - Ettefaghi, Ehsanollah; Ghobadian, Barat; Rashidi, Alimorad; Najafi, G.; Khoshtaghaza, Mohammad Hadi; Rashtchi, Maryam; Sadeghian, Sina
Abstract: Nowadays, energy is the most challenging issue in the world. Although nanotechnology has been promising in offering huge developments in various fields, there are still concerns about the potential threats of nanotechnology products and applications. The concerns are mostly about the possible entrance of nanoparticles into body and their toxicity. As metallic and metal oxide nanoparticles might have toxic effects on living organisms, the use of biocompatible nanoparticles can considerably reduce these concerns. In this research, a combination of diesel-biodiesel-water-biodegradable nanoparticles was used to optimize fuel consumption, reduce pollutants, and enhance diesel engine performance for first time. Carbon quantum dot nanoparticles were synthesized through the hydrothermal method using orange peel and were then characterized thoroughly. Water and quantum dot nanoparticles were added to the B15 fuel (diesel fuel containing 15% biodiesel) in various concentrations. Then, engine performance experiments were performed using a single cylinder engine to investigate functional parameters and assess exhaust pollutants. The obtained results showed that the addition of water and quantum dot nanoparticles to the B15 fuel causes an increase in engine torque and power and decreases the brake specific fuel consumption. This is due to the better mixing of the fuel and air in combustion chamber and provision of more oxygen. It was also revealed that the use of emulsion nanofuels decreases the emission of unburned hydrocarbons and nitrogen oxides (NOx ). By employing the B15W5-CQD60 fuel (B15 fuel containing 5% water and 60 ppm carbon quantum dots), diesel engine power at the rate of 2700 rpm was increased by 21% compared with the B15 pure fuel. Furthermore, using the B15W10 fuel (B15 fuel containing 10% water), NOx emission was decreased by 25% on average compared with the B15 pure fuel.